The Effect of Intellectual Capital, Behavior Direction, Effort Level, and Persistence Level on Employee Performance as an Effort to Improve Productivity at PT. Global Offset Sejahtera - Julio Alfi Kartika Putra, Julio Alfi Kartika Putra; Pratama, Devangga Putra Adhitya; Hendriawan, Ayi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study examines the role of intellectual capital in enhancing work productivity by focusing on three aspects of employee behavior: the direction of their actions, the amount of effort they put in, and their level of persistence. The research is conducted at PT. Global Offset Sejahtera, a printing company based in Sidoarjo. Intellectual capital is considered an intangible resource made up of the knowledge, skills, and capabilities of individuals and the organization as a whole. These elements help in achieving company objectives in a more effective and efficient manner. The study included 200 employees as participants and used a quantitative method along with SPSS for data analysis. The findings reveal that the three behavioral dimensions significantly impact employee productivity. This suggests that building intellectual capital not only enhances individual thinking abilities but also shapes how employees behave, how hard they work, and how long they persist in their tasks. As a result, it is recommended that companies adopt strategies for managing intellectual capital that are closely linked to efforts aimed at improving employee behavior, in order to support long-term productivity growth.